(NmAGNITOSOPRQVENNYE GEOFIZI^ESKIE QWLENIQ (B/s - (NiVOWKINA(B, (Nn(B.(Ni(B.s; (NkANONIDI(B, (NhARLAMPIJ dMITRIEWI^s; (NoSIPOW(B, (NnIKOLAJ kONSTANTINOWI^s; (NlUGOWENKO(B, (Nw(B.(Nn(B.s ((NmOSKWA (B:s (Nizmiran(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE GLAWs
Keywords: (NzEMNOJ MAGNETIZMs